Efectos del malteado y variedad de maíz en las características fisicoquímicas y sensoriales en una bebida refrescante - Ormaza Loor, Gema Monserrate (2021)
The objective of this research was to determine the effects of malting and corn varieties on the physicochemical and sensory characteristics of a refreshing drink. A completely randomized design (DCA) was applied in a bifactorial arrangement A x B, with factor A being three varieties of corn and factor B being the condition of the corn (malted and unmalted), obtaining 6 treatments and three repetitions were carried out, resulting in 18 units of refreshing drink of 2000 ml experimental. The variables evaluated were: physicochemical (pH, acidity, Brix degrees and suspended solids) where significant differences were detected between the drinks in relation to pH, acidity and Brix degrees, obtaining T1, T3 and T5 as the best treatments, these being matted condition; in the sensory analyzes (general quality) performed by the ranking test, T5 was the best treatment; In the microbiological tests carried out on the drink on total coliforms, Escherichia coli, molds and yeasts, it reflected absence.